A Vector Autoregressive Analysis of Economic Globalization and Economic Growth Relationship in Nigeria - Madubuike, K.O; Kalu, C.U (Social Science Research, 2022)
In reality, however, globalization has its winners and losers. There are compliant s of rising job losses and unemployment, higher inflation, inequality in growth, worsening balance of payments and shrinking share of manufactured export base. Therefore, this study examined the impact of economic globalization on economic growth in Nigeria from 1986 to 2020 using the both the vector error correction model and vector autoregressive approaches. The variables used are real GDP as the dependent variable, and trade openness, quality of governance, school attainment, life expectancy, foreign direct balance as independent and control variables. The results show that the coefficients of secondary school attainment, life expectancy, gross fixed capital formation and fiscal balance appeared negatively related to economic growth. The study recommend among others, the need for the government to promote human capital in Nigeria through greater fiscal allocation to the health and education sectors as well as promoting the business environment in Nigeria through the provision of infrastructure.